Hold me closer, necromancer / 1. - McBride, Lish (Necromancer Series, 2010)
Sam LaCroix, a Seattle fast-food worker and college dropout, discovers that he is a necromancer, part of a world of harbingers, werewolves, satyrs, and one particular necromancer who sees Sam as a threat to his lucrative business of raising the dead.